Clinical and nonclinical factors associated with a complete family history in a statewide quality improvement consortium. Issue 28 (1st October 2022) - Weiner, Shayna; Liu, Manlan; Rizzo, Elizabeth; Griggs, Jennifer J.
Abstract : 149 Background: A complete family history is critical in identifying cancer patients who should be referred to genetic counseling and testing. Despite the importance of a detailed family history, defined as any cancer diagnoses in first- or second-degree relatives and their age at diagnosis, only about one third of cancer patients have a complete family history documented in their medical record. The Michigan Oncology Quality Consortium (MOQC), a physician-led consortium of oncology practices across the state of Michigan, selected documentation of a complete family history in oncology patients as a quality measure. The purpose of this study was to identify clinical and non-clinical factors associated with the quality of the family history. Methods: Beginning in 2020, MOQC began collecting completeness of documentation of cancer family history from the medical oncology records of patients with invasive cancer from MOQC practices twice per year in the Quality Oncology Practice Initiative (QOPI) database. QOPI data from 2020 and 2021 were combined for analyses. A multivariate model was built to determine the clinical and non-clinical factors, including age, sex, race, ethnicity, and cancer diagnosis, associated with documentation of a complete family history. Results: Between January 2020 and December 2021, 10, 800 patients' records were abstracted. Of these, 30% had a complete family history documented in their medical record. Factors independently and significantly associated with not having a complete family history included increasing age and Black race. Patients with breast cancer (AOR 1.94, 95% CI 1.72, 2.19) and colorectal cancer (AOR 1.2, 95% CI 1.05, 1.37) were more likely to have a complete family history than all others. Patients with prostate, pancreas, or endometrial cancer—all of which are associated with cancer syndromes—were no more likely than other patients to have a complete family history. Sex and ethnicity were not significantly associated with documentation of a complete family history. Conclusions: Patients may qualify for genetic testing based on family history alone. It is therefore crucial that clinicians know a patient's complete family history to identify those patients eligible for genetic risk assessment. We have identified gaps in the quality of the family history with increasing age, in Black patients, and, except for breast and colorectal cancer, in patients with cancers associated with an inherited susceptibility. Our findings highlight an opportunity to improve care.Patient Characteristic AOR 95% CI Age (continuous) 0.99 (0.988, 0.995) Race Black 0.76 (0.66, 0.87) Asian 0.94 (0.66, 1.33) White Referent Native American 0.92 (0.50, 1.72) Alaska Native/Pacific Islander 1.34 (0.35, 5.05) Hispanic ethnicity 1.39 (0.99, 1.32) Female .096 (0.84, 1.09) AOR, adjusted odds ratio; 95% CI, 95% confidence interval.